From Swipe to Stay: How Digital Banking Service Quality Drives Customer Retention through Customer Satisfaction - Lama , Juna; Kayestha , Mijala (Journal of Innovation in Academia, 2025)
While the adoption of digital banking continues to rise, research on how digital service quality affects customer retention is limited. This study applies an E-S-QUAL-based framework to assess how dimensions of digital banking service quality (DBSQ) influence customer satisfaction and their mediating role in customer retention within commercial banks in Kathmandu Valley. A cross-sectional design was used, collecting data from 426 respondents through structured questionnaires and analyzed through SmartPLS 4.0. Results show that among the five DBSQ dimensions, efficiency, ease of use, and security significantly affect customer satisfaction. Customer satisfaction, in turn, has a significant impact on customer retention and partially mediates the relationship between service quality and retention. These findings highlight the critical role of digital service quality in enhancing customer satisfaction and loyalty. The study offers valuable insights for banks and policymakers aiming to improve digital banking experiences to foster stronger customer retention.